Single Nucleotide Polymorphisms (SNPs) of COL1A1 and COL11A1 in Class II Skeletal Malocclusion of Ethnic Javanese Patient - Ardani IGAW; Aulanni'am; Diyatri I (Dove Medical Press, 2020)
I Gusti Aju Wahju Ardani,1 Aulanni’am,2 Indeswati Diyatri3 1Orthodontics Department, Faculty of Dental Medicine, Airlangga University, Surabaya, Indonesia; 2Biochemistry Department, Faculty of Veterinary Medicine, Brawijaya University, Malang, Indonesia; 3Oral Biology, Faculty of Dental Medicine, Airlangga University, Surabaya, IndonesiaCorrespondence: I Gusti Aju Wahju ArdaniOrthodontics Department, Faculty of Dental Medicine, Airlangga University, Surabaya, IndonesiaTel +623 15030255Email wahju_ardani@fkg.unair.ac.idBackground: The prevalence of malocclusion cases in the orthodontic specialist clinic in Airlangga University’s Dental Hospital in Surabaya, Indonesia, in 2014– 2016 is fairly high, as 55.34% of the occurrences were identified as class II skeletal malocclusion. This type of skeletal malocclusion, which is usually recognized in adults, occurs as a result of variation during growth and development. Lately, there have been many reports on gene polymorphisms of COL1A1 and COL11A1, which are assumed to be associated with class II skeletal malocclusion in Caucasians.Purpose: This study aims to analyze the relationship between single nucleotide polymorphisms (SNPs) of COL1A1 and COL11A1 with class II skeletal malocclusion in Javanese ethnic group patients with mandibular micrognathism.Materials and Methods: The diagnosis of class II skeletal malocclusion was established using the lateral cephalometric radiographs (ANB angle ≥ 4°) (n=50). DNA was extracted from the patient’s peripheral blood. After that, PCR, electrophoresis, and DNA sequencing were conducted on the extracted DNA based on COL1A1 and COL11A1 primers.Results: The SNPs in COL1A1 are c.20980G/A in 27 patients and c.20980G>A in 8 patients, whereas SNPs in COL11A1 are both c.134373C/A and c.134555C/T in 8 patients and both c.[134373A>C] and c.134582G>A in 10 patients. All samples show the deletion (c.[134227delA]) in COL11A1.Conclusion: SNPs in COL1A1 and COL11A1 have been found in class II skeletal malocclusion of Javanese ethnic group patients. Seventy percent of SNPs in COL1A1 occur in rs.2249492, whereas 36% of newly discovered SNPs appear in COL11A1. All samples also have deletion in COL11A1.Keywords: COL1A1, COL11A1, class II malocclusion, mandibular micrognathism, ethnic Javanese